Pragmatics of Diplomatic Speeches Delivered in UN’s Security Council in 2023: systemic characteristics - Гольцева, Марія (Studia Philologica, 2024)
Abstract. The article examines the system of pragmatic intentions of diplomatic participants in their speeches during the meetings of the UN Security Council in 2023. As a result, this research contributes to a better understanding and identification of the speaker’s intentions in their diplomatic speech, and participation in discussions after the main speech. It has been established that declarative and referential intentions have the highest frequency in 2023, which indicates the desire of participants in diplomatic communication to clearly state their position and reduce the ambiguity in interpretation. Directive intentions are rarely used, which is explained by diplomatic ethics. Also, it has been proposed a hierarchy of pragmatic intentions according to the universal model of open systems. The relevance of the research is determined by the need to improve communicative interactions and, as a result, to improve negotiations, making the most optimal decisions, and adopting resolutions.